Enhancing Motivation to Learn Mathematics Among Elementary School Children at Pondok X - Duarsa, Naraya Kinastrian Siniddhikara; Ismana, Arsy Febrianti Putri; Azzuhruf, Naura Reisya; Wibowo, Astri Anggraini Hapsari (Jurnal Indonesia Sosial Sains, 2025)
This research aimed to enhance the motivation of elementary school children aged 7-11 years at Pondok X in learning Mathematics through interactive and engaging methods. The research employed a pre-test and post-test design, with a learning motivation questionnaire encompassing six key indicators: (1) desire to succeed, (2) learning drive, (3) future expectations, (4) recognition in learning, (5) interest in learning activities, and (6) a conducive learning environment. The results showed a notable increase in motivation, particularly in the areas of desire to succeed, internal learning drive, and future aspirations. The interventions, including educational games such as "Mathematics Snake and Ladder," "Flash Cards," "Congklak," and "Audio-Visual Media," contributed to creating a more engaging and enjoyable learning experience. These methods, tailored to the cognitive development stages of children, proved effective in boosting their enthusiasm for learning Mathematics. The findings underscore the importance of using age-appropriate, interactive learning tools to foster positive learning behaviors. The research has practical implications for educators seeking to improve student engagement and academic performance in Mathematics.